PENGARUH MANDI UAP REMPAH NUSANTARA TERHADAP PENINGKATAN IMUNITAS TUBUH PASIEN COVID-19 DI LAMPUNG TENGAH - Nyang Vania Ayuningtyas Harini; Yeyen Ilmiasari (AgriMalS, 2021)
Coronavirus disease (Covid19) is an infectious disease caused by the SARSCoV2 virus. Most people infected with COVID-19 show mild to moderate symptoms and recover without specific treatment. According to the monitoring results of the Lampung Provincial government, patients with Covid-19 cases in Lampung until June reached 57110 people. Patients with Covid-19 cases in Central Lampung until June 2022 reached 4,549 people. The main thing we need to know is that we will easily catch the Covid-19 virus if our immune system decreases. One alternative to increase the body's immunity is to take a spice steam bath or often referred to as an archipelago spice sauna. The Nusantara Spice Sauna is a therapy that uses warm steam as a medium. People undergoing this therapy will be placed in specially designed cubicles. This research was conducted in Gunung Sugih, Central Lampung Regency, RSUD Demang Island Raya from July – August 2021. The study used a simple randomized method for the number of Covid-19 patients. The main variables are counting the number of patients exposed to the Covid-19 virus and counting the number of patients who experience changes after taking the archipelago spice steam bath. For this experiment, the number of samples was 30 people who were exposed to the Covid-19 virus. In the fourth week, many patients have experienced a change for the better. Both in terms of health (negative Covid-19) and psychology. It is suspected, with the steam bath of Nusantara spices, the patient will excrete toxins in the body through sweat. In addition, the spice steam contains essential oils (essential oils) that can cleanse the internal organs of the body (detox). The warm steam also produces aromatherapy which increases the relaxing effect. reduce stress levels and increase body immunity so that the body is exposed to the Covid-19 virus. In the fourth week, many patients have experienced a change for the better. Both in terms of health (negative Covid-19) and psychology. It is suspected, with the steam bath of Nusantara spices, the patient will excrete toxins in the body through sweat. In addition, the spice steam contains essential oils (essential oils) that can cleanse the internal organs of the body (detox). Aromatherapy produced from warm steam can increase the relaxation effect, reduce stress levels and increase body immunity so that the body is not exposed to the Covid-19 virus.